Erythema Multiforme Exudativum - Lyle, William M (Canadian Journal of Optometry, 1980)
Erythema multiform is an unusual but potentially serious reaction which develops in a few patients. It is believed to be an immune response to certain drugs or to other stimuli. The Stevens-Johnson syndrome represents the ocular manifestations when the reaction involves the mucous membranes. Penicillin has in rare instances precipitated erythema multiforme and requires that those who administer it be aware of this potential and be prepared to treat the patient if such an unwanted development occurs.